The first draft reference genome of the American mink (Neovison vison). Issue 1 (December 2017) - Cai, Zexi; Petersen, Bent; Sahana, Goutam; Madsen, Lone; Larsen, Knud; Thomsen, Bo; Bendixen, Christian; Lund, Mogens Sandø; Guldbrandtsen, Bernt; Panitz, Frank
Abstract The American mink (Neovison vison ) is a semiaquatic species of mustelid native to North America. It's an important animal for the fur industry. Many efforts have been made to locate genes influencing fur quality and color, but this search has been impeded by the lack of a reference genome. Here we present the first draft genome of mink. In our study, two mink individuals were sequenced by Illumina sequencing with 797 Gb sequence generated. Assembly yielded 7, 175 scaffolds with an N50 of 6.3 Mb and length of 2.4 Gb including gaps. Repeat sequences constitute around 31% of the genome, which is lower than for dog and cat genomes. The alignments of mink, ferret and dog genomes help to illustrate the chromosomes rearrangement. Gene annotation identified 21, 053 protein-coding sequences present in mink genome. The reference genome's structure is consistent with the microsatellite-based genetic map. Mapping of well-studied genes known to be involved in coat quality and coat color, and previously located fur quality QTL provide new knowledge about putative candidate genes for fur traits. The draft genome shows great potential to facilitate genomic research towards improved breeding for high fur quality animals and strengthen our understanding on evolution of Carnivora.